Case report: A rare occurrence of triple malignancy of the stomach, rectum and liver in a single patient - Jin, Cancan; Hu, Jiangnan; Balapattabi, Kirthikaa; Wang, Brian; Hu, Sizhe; Wang, Kangyi; Fu, Liangbin; Zhao, Xiaokang; Qian, Feng; Wang, Zhen (Frontiers in Oncology, 2022)
Malignant tumors of the digestive system are common worldwide; however, it is extremely rare for more than two malignancies to occur simultaneously. Here, we report a case with a triple malignancy of the digestive system, including gastric, rectal, and hepatic tumors. The patient underwent surgical resection of three tumors followed by chemotherapy. Negative image-based screenings and the absence of serum tumor biomarkers elevation were found at 2.5 years after the surgery, indicating the absence of recurrence and metastasis of cancers.